2021
DOI: 10.3390/pr9071148
|View full text |Cite
|
Sign up to set email alerts
|

CFD-Based Structural Optimization of Rotor Cage for High-Efficiency Rotor Classifier

Abstract: Due to the uneven materials dispersion and high dust concentration in industrial applications of turbo air classifiers, a high-efficiency rotor classifier was designed. Numerical simulations by ANSYS-Fluent 19.0, the effects of rotor cage shape, the number of blades, and the blade profile on the inner flow field, as well as classification performance, were investigated. The simulation results indicated a significant improvement in flow field distribution near the classification surface with the conical rotor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Using the differences in physical and chemical properties of each component in the mixture, the process of distributing each component to different spatial regions is called separation. Typical applications include the cyclone separator [50][51][52][53], hydrocyclone [54,55], classifier [56][57][58], filter [59][60][61][62] and dust collector [63,64]. In the separation process, CFD-DPM is used to obtain the fluid and particle behavior in the internal space, so as to further study the separation performance [65][66][67].…”
Section: Separationmentioning
confidence: 99%
“…Using the differences in physical and chemical properties of each component in the mixture, the process of distributing each component to different spatial regions is called separation. Typical applications include the cyclone separator [50][51][52][53], hydrocyclone [54,55], classifier [56][57][58], filter [59][60][61][62] and dust collector [63,64]. In the separation process, CFD-DPM is used to obtain the fluid and particle behavior in the internal space, so as to further study the separation performance [65][66][67].…”
Section: Separationmentioning
confidence: 99%
“…The physical model is the pneumatic classifier. Its main working principle and structure are described in the literatures [29,30]. The data transmission layer includes the operating status data of the classifier, the sensor data and so on, and these multi-source heterogeneous data is integrated and processed to obtain the twin data and realize data sharing and interaction.…”
Section: Digital Twin Design Of Pneumatic Classifiermentioning
confidence: 99%
“…Aiming at the problems of uneven material dispersion and serious wear of guide vanes, some scholars researched and designed a new rotor classifier and carried out numerical simulation and optimization of the internal structure [25][26][27]. To date, although many studies have been carried out to optimize the operating parameters, the results presented showed that there are differences in the optimum operating parameters for different classifiers and materials, and few studies have been reported on the calcined petroleum coke classification experiments.…”
Section: Introductionmentioning
confidence: 99%